Bottom-Up or Top-Down Local Service Delivery? Assessing the Impacts of Special Districts as Community Governance Model. Issue 1 (January 2021) - An, Brian Y.
This article assesses the impacts of bottom-up local governing institutions relative to top-down bureaucracies in local service delivery. Community services districts (CSDs) in California, a class of special districts that provides various neighborhood-level services, are examined to answer this question. An innovative characteristic of this institutional form is that it is residents who create them through a grass-root collective action to achieve a bottom-up governance structure, after opting out from a county service system. With changes in residential property values as performance metrics, the quantitative analysis utilizes district formation events and features a hedonic difference-in-difference regression. The results show that the creation of CSDs produces more significant impacts on property values than county authorities do. Yet, the effects are heterogeneous across the communities when the analysis is further drilled down to each district. The exploratory qualitative case study then uses interview data with district managers and document analysis to unveil what administrative factors explain the success and failure trajectory of bottom-up institution management. The case study identifies such factors as critical codeterminants, including managerial and board leadership, clarity of a problem statement, public support, and intergovernmental coordination with county and state agencies.